2022
DOI: 10.3390/ma15030744
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Basalt Fibers on the Crack Resistance of Asphalt Mixtures and Mechanism Analysis

Abstract: The paper aims to investigate the influence of basalt fiber (BF) on the crack resistance of the asphalt mixture and conduct a mechanical analysis. First, two typical asphalt mixtures, namely AC-13 and SMA-13, were designed. The impact of BF on the mixture design results was analyzed. Then, several macroscopic tests, namely the four-point bending test, indirect tensile test, and semicircular bending test (SCB), were conducted to assess the effect of BF on the cracking resistance of asphalt mixtures. Finally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…This illustrates that the optimum fiber length is related to the aggregate spacing, influenced by the mix grading [ 60 ]. In the four-point bending fatigue test, Wu et al [ 56 ] discovered that the improvement of BF on fatigue life is approximately three times in AC and four times in SMA, indicating that the increase of BF is more substantial in SMA.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…This illustrates that the optimum fiber length is related to the aggregate spacing, influenced by the mix grading [ 60 ]. In the four-point bending fatigue test, Wu et al [ 56 ] discovered that the improvement of BF on fatigue life is approximately three times in AC and four times in SMA, indicating that the increase of BF is more substantial in SMA.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
“…The SCB test obtained the maximum fracture toughness value by adding 0.3% BF to the asphalt mixture, and 4 mm BFs were better than 8 and 12 mm [ 54 ]. The SCB test findings of the experiment by Wu et al [ 56 ] were that the addition of BF increased the fracture energy of AC-13 and SMA-13 by 36% and 38%, respectively. Pei et al [ 70 ] combined the results of low-temperature beamlet bending test, IDEAL cracking test, and SCB test to conclude that for AC-13, BFs with a diameter of 7 μm had the best reinforcement effect on the crack resistance of the mixture.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
“…It was revealed that the anti-tensile performance of asphalt mixture mainly depends on the bonding strength between asphalt mortar and aggregate [ 21 ]. The bonding strength is reported to be closely associated with basic indexes of asphalt mortar, such as viscosity and dynamic shear modulus, which can vary after fiber incorporation [ 22 , 23 , 24 , 25 ]. Therefore, fiber dosage is an important issue that needs to be taken into consideration for a favorable tensile performance.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor evaluation methods for the tensile performance of asphalt mixture mainly include the indirect tension test [ 26 , 27 , 28 ], bending beam test [ 29 , 30 ], semi-circular bending test [ 23 , 31 ], and direct tension test [ 32 ]. Research by direct tension test is scarce, and studies on fiber-reinforced asphalt mixture by direct tension test are even fewer.…”
Section: Introductionmentioning
confidence: 99%
“…An infrared thermal imager is used to monitor the peak temperature of weld joint during FRW. Three-point bending tests [31][32][33] and impact tests [34,35] are applied to evaluate the mechanical properties of the specimens after FRW. Optical microscopy, energy dispersive spectroscopy, and field-emission scanning electron microscopy were used to investigate the microstructure of welding zone.…”
Section: Introductionmentioning
confidence: 99%